ANALISIS STRATEGI PENGELOLAAN SAMPAH DI KOTA SEMARANG - Rasyid Abdillah; Dyah Hariani; Rihandoyo Rihandoyo (Journal of Public Policy and Management Review, 2014)
Semarang city is the capital of Central Java is sufficiently developed, the rapid development of the city followed by volume increases in population resulting in the amount of waste produced is increasing. However, waste management facilities and infrastructures owned by the city of Semarang is not proportional to the increase in the volume of the garbage. The problem that arises : How to waste management in the city of Semarang at this time, and what are the factors supporting and inhibiting factors ? How should the alternative strategies for the optimization of waste management in the city of Semarang ?. The purpose of this study was to describe the waste management, and what are the factors that support and hinder the application of waste management. Furthermore, the data obtained are used to formulate an alternative strategy of waste management in the city of Semarang. Attempts to answer issues and research purposes is done by using the theory of strategic management as a basic foundation in analyzing and formulating strategies. To identify strengths, weaknesses, opportunities, and threats as well as to evaluate the strategic issues using the SWOT analysis and the litmus test. Once the analysis is done, shows there are eight strategic issues in the implementation of the waste management. And after an evaluation by a litmus test, it can be seen the three most strategic issues can be found. It is maximize community empowerment related vision and mission to be achieved,  multiply the number of fleet and containers in Semarang in order to improve service to the public, and increase public participation in order to overcome the limitations of the available fleet and containers.